PENERAPAN PERHITUNGAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI PT. GLOBAL BAHTERA LOGISTIK DI SAMARINDA - Cahyanti, Fitri; Mardiana, Mardiana; Verahastuti, Camelia (RJABM (Research Journal of Accounting and Business Management), 2020)
Value Added Tax is one type of tax that became the mainstay of the government in order to realize the independence of the nation in development.This research purpose to know The Application, Calculation and Reporting of Value Added Tax at PT. Global Bahtera Logistik in Samarinda implement already apply obligation of Value Added Tax obey Value Added Tax Law number 42 year 2009.Analysis tools used in this research is Value Added Tax Law number 42 year 2009 about Value Added, goods and services and sales tax on luxury goods. Data obtained by using the technique of documentacion and observation.The results obtained from the details of the bill invoice and faktur Value Added Tax at PT. Global Bahtera Logistik in Samarinda it was found, have not done the rectification of the notice Value Added Tax period from march to desember 2018.The conclusion of this research that The Application, Calculation and Reporting of Value Added Tax at PT. Global Bahtera Logistik in Samarinda not in accordance with the Value Added Tax Law Number 42 Year 2009.